Tolerated Failure or Missed Opportunities and Potentials for Teacher Leadership in Urban Schools? - Jumanne R. Sledge; Pamela Morehead (Arizona State University, 2015)
This monograph examines the existing role of teacher leaders while addressing many of the missed opportunities for teacher leaders to impact student achievement. The work of teacher leaders must impact teacher expectations, teacher content knowledge base, and teacher practice. In an era of teacher accountability and teacher quality schools can no longer continue to tolerate the fact that 40 percent of students in urban and rural schools never make it to high school graduation. To that end, urgency suggests that we begin to examine the potential of teacher leadership.